Konsep Kompetensi Keperawatan dalam Praktik Telenursing - Nurullia Hanum Hilfida; Muhammad Miftahussurur; Hanik Endang Nihayati (Journal of Telenursing (JOTING), 2023)
This study aims to describe the development of nursing competency in telenursing practice. The method used is a systematic review by collecting articles through the Scopus, Science Direct, PubMed, and Google Scholar databases with publications starting in 2020-2023. Articles were selected with PRISMA based on predetermined inclusion and exclusion criteria, using telenursing, telehealth nursing, telecommunication nurse, and nurse competency. The results showed that there were 279 articles consisting of 17 Scopus articles, 10 Science Direct articles, 16 PubMed articles, and 9 Google Scholar articles. Based on the analysis, 15 full-text articles met the inclusion criteria for review. The study's results show that nursing competence in telenursing consists of social competence, personal competence, professional and methodological competence, telenursing etiquette, and telenursing practice framework during consultations between patients and nurses. In conclusion, telenursing competence must be implemented in telenursing practice readiness to improve nursing services. Keywords: Nursing Competence, Nurse, Practice, Telenursing